An Efficient Spectral Method for Acoustic Scattering from Rough Surfaces (Communications in Computational Physics, 2007)
An efficient and accurate spectral method is presented for scattering problemswith rough surfaces. A probabilistic framework is adopted by modeling the surfaceroughness as random process. An improved boundary perturbation technique isemployed to transform the original Helmholtz equation in a random domain into astochastic Helmholtz equation in a fixed domain. The generalized polynomial chaos(gPC) is then used to discretize the random space; and a Fourier-Legendre methodto discretize the physical space. These result in a highly efficient and accurate spectralalgorithm for acoustic scattering from rough surfaces. Numerical examples arepresented to illustrate the accuracy and efficiency of the present algorithm.